2012
DOI: 10.5740/jaoacint.12-050
|View full text |Cite
|
Sign up to set email alerts
|

GMOMETHODS: The European Union Database of Reference Methods for GMO Analysis

Abstract: In order to provide reliable and harmonized information on methods for GMO (genetically modified organism) analysis we have published a database called "GMOMETHODS" that supplies information on PCR assays validated according to the principles and requirements of ISO 5725 and/or the International Union of Pure and Applied Chemistry protocol. In addition, the database contains methods that have been verified by the European Union Reference Laboratory for Genetically Modified Food and Feed in the context of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 0 publications
0
40
0
2
Order By: Relevance
“…W tym celu stosowano metody specyficzne dla poszczególnych linii GMO, zwalidowane i uznane za zalecane do badań GMO w całej Unii Europejskiej. Do identyfikacji linii GMO i oznaczenia jej zawartości stosowano metody wykorzystujące technikę real-time PCR (1,4). (10,11).…”
Section: Materiał I Metodyunclassified
“…W tym celu stosowano metody specyficzne dla poszczególnych linii GMO, zwalidowane i uznane za zalecane do badań GMO w całej Unii Europejskiej. Do identyfikacji linii GMO i oznaczenia jej zawartości stosowano metody wykorzystujące technikę real-time PCR (1,4). (10,11).…”
Section: Materiał I Metodyunclassified
“…or '-' symbols. GM events not detected by any screening method or not detected by the original screening set of Waiblinger et al (2010) are indicated by grey shading a An authorization decision is taken or is pending b QT-ELE-00-004 (Bonfini et al 2012) c QL-ELE-00-011 (Bonfini et al 2012) d QL-ELE-00-014 (Bonfini et al 2012) e QL-CON-00-008 (Bonfini et al 2012) f QL-CON-00-011 (Bonfini et al 2012) g QT-ELE-00-002 (Bonfini et al 2012) h QL-ELE-00-016 (Bonfini et al 2012) i QL-ELE-00-015 (Bonfini et al 2012) J Not detected by any screening method a FAM and HEX signal) can be analysed in one reaction. Furthermore, in case of a positive finding for a sample DNA, the subsequent analysis for identification is less complex if only a FAM or HEX signal is detected.…”
Section: Assay Design and Optimisationmentioning
confidence: 99%
“…At the time we began the study, six GMO soybean events (MON 87701,MON 87708,MON 87769, were identified as not being covered by the Waiblinger screening table. Protocols for six single event-specific real-time PCR methods using fluorescein amidite (FAM) labeled TaqMan probes and certified reference materials are publicly available (Bonfini et al 2012). If the six methods combine in one PCR reaction, a positive FAM fluorescence signal would indicate a positive screening result for at least one of the GM soybean events, without knowing specifically which of the GM event(s) actually is present in the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the authors claim, confirming the transgenic Biodivers Conserv (2018) 27:539-566 543 Table 1 Evidence table of sampling In searching for p35-S and T-NOS, Quist and Chapela were applying a screening method based on primers that target common elements of many commercial transgenic constructs. This is still the most widely applied screening matrix worldwide (Bonfini et al 2012;Block et al 2013). The method of nested-PCR was used to confirm non-specific binding and the amplification of unexpected primer binding sites.…”
Section: Transgenes In Mexican Maizementioning
confidence: 99%